Developmental arrest in Drosophila melanogaster caused by mitochondrial DNA replication defects cannot be rescued by the alternative oxidase - Rodrigues, Ana Paula C. [UNESP]; Camargo, Andre F. [UNESP]; Andjelkovic, Ana; Jacobs, Howard T.; Oliveira, Marcos T. [UNESP] (Nature Publishing Group, 2018)
The xenotopic expression of the alternative oxidase AOX from the tunicate Ciona intestinalis in diverse models of human disease partially alleviates the phenotypic effects of mitochondrial respiratory chain defects. AOX is a non-proton pumping, mitochondrial inner membrane-bound, single-subunit enzyme that can bypass electron transport through the cytochrome segment, providing an additional site for ubiquinone reoxidation and oxygen reduction upon respiratory chain overload. We set out to investigate whether AOX expression in Drosophila could counteract the effects of mitochondrial DNA (mtDNA) replication defects caused by disturbances in the mtDNA helicase or DNA polymerase gamma. We observed that the developmental arrest imposed by either the expression of mutant forms of these enzymes or their knockdown was not rescued by AOX. Considering also the inability of AOX to ameliorate the phenotype of tko(25t), a fly mutant with mitochondrial translation deficiency, we infer that this alternative enzyme may not be applicable to cases of mitochondrial gene expression defects. Finding the limitations of AOX applicability will help establish the parameters for the future putative use of this enzyme in gene therapies for human mitochondrial diseases.